(untitled) (Conferencea, 2024)
The article explores the application of synergetic methodology in understanding the philosophical legacy of Central Asian thinkers and its relevance to the development of New Uzbekistan. This approach provides a holistic framework for analyzing societal changes, with a focus on maintaining stability, spiritual renewal, and individual development. Drawing on the teachings of figures such as Farabi, Ibn Sina, and others, the article underscores the role of education, science, and morality in shaping a prosperous society. The synergy between national identity, cultural heritage, and modern strategies is essential for navigating the current period of transformation and ensuring the nation’s progress.